1995
DOI: 10.1002/app.1995.070581023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated low earth orbit radiation on polyimides (UV degradation study)

Abstract: UV degradation of polyimide films in air and vacuum were studied using UV‐visible, ESR, FTIR, and XPS spectroscopies. The UV‐visible spectra of polyimide films showed a blue shift in the absorption compared to Kapton. This behavior was attributed to the presence of bulky groups and kinks along the polymer chains which disrupt the formation of a charge‐transfer complex. The UV‐visible spectra showed also that UV irradiation of polyimides result extensively in surface degradation, leaving the bulk of the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 11 publications
4
27
0
Order By: Relevance
“…13 The UV light degrades polymer substrates; therefore, a UV filter was used to eliminate wavelengths under 380 nm. 14 The spectral distribution of the xenon flash lamp from 380 nm and 1000 nm for 50 J/cm 2 irradiation is shown in Fig. 4.…”
Section: Ipl System Setup and Sintering Conditionsmentioning
confidence: 99%
“…13 The UV light degrades polymer substrates; therefore, a UV filter was used to eliminate wavelengths under 380 nm. 14 The spectral distribution of the xenon flash lamp from 380 nm and 1000 nm for 50 J/cm 2 irradiation is shown in Fig. 4.…”
Section: Ipl System Setup and Sintering Conditionsmentioning
confidence: 99%
“…1 It has been used to study the degradation of polymers, 2,3 brought about by radiation in a vacuum, 4,5 photooxidation, 6 simulated low earth orbit environments, 7,8 degradation in solution 9,10 , ageing after plasma treatment 11 and in natural weathering situations. 12,13 The aim of this study was to determine if XPS is a useful technique for detecting the early stages of powder coating deterioration, specifically polyester coatings, which can lead to a lack of corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…This result is suggested that chemical bond (C-C, C-O, C-H) cleavage reaction was occurred and modified on PET, PI and PEEK surfaces by UV exposure. [29][30][31] Therefore, the polar protic moieties of oxidized species are formed and achieved the selective electroless plating.…”
Section: Resultsmentioning
confidence: 99%